Financial analysis of TL Geosciences Sdn Bhd and its relation with the level of company performance / Noruladila Mohd Ramli - Mohd Ramli, Noruladila (2011)
Measuring business performance is an important aspect in determining the level of company performance. In order to strive in the most competitive industry which involved millions of Ringgits, a company has to continuously adapting or implementing the best strategies for them to gain competitive advantage over their competitors. Although measuring the business performance would involve certain level of cost and time consumed, it is the best way to develop the business to the new level other than enable the management to know their level performance as compare to their competitors. This research focus on measuring the financial performance of TL Geosciences Sdn Bhd, a subsidiary of Sapura crest Petroleum, an oil and gas industry service provider over their competitors which are Asian Geos Sdn Bhd and Offshore Geo-survey Sdn Bhd based on certain analyses. These three companies are Malaysian based companies that mainly involved in Geotechnical Engineering Services. As they provide the same services and serve the same clients such Petronas Carigali, Sarawak Shell, Petro Vietnam, McDermott and many other oil and gas companies, they have to be the best among them in term of work efficiency and service quality. The research will be using the historical data gain from the financial reports from internal and external of the company. The result of the analyses will be able to assist the management of the company in developing the best strategy for the benefit of the company. In this research as various analyses such ratio and common size analyses are done to determine the performance of the company in term of their previous performance and also competitors.